3D kinematics in alpine Skiing in alpine skiing: A comparison of a full body inertial measurement system and an optical video based system - Krüger, A.; Edelmann-Nusser, J. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: So far the analysis of the skiing techniques in alpine skiing has been often limited to the use of optical video based methods. Due to the ongoing miniaturization, the application of inertial measurement systems (IMS) is becoming increasingly practicable. The investigations of Brodie et al. (2008) and Supej (2007) examined the application of a full body IMS for the determination of kinematic parameters in alpine skiing. However, a quantitative validation of a full body IMS for the application in a real skiing environment is so far not available. The purpose of this study was to determine the accuracy of a full body inertial measurement system for the application in alpine skiing in comparison to an optical video based system.